Carbon Stock and CO₂ Sequestration Potential of Terminalia mantaly as a Conservation Effort in the Campus Forest of the State University of Surabaya - Gita Rizki Anggraini; Fida Rachmadiarti; Tarzan Purnomo; Tri Lestari Saidha Rohmah (Biocaster : Jurnal Kajian Biologi, 2026)
Carbon stocks in campus forests play an important role in maintaining ecosystem balance and supporting climate change mitigation. This study aims to analyze the biomass, carbon stock, and carbon sequestration of Terminalia mantaly, along with the contributing factors that influence them. This research employed a non-destructive measurement with purposive sampling. The relationship among variables was analyzed using pearson correlation. The result showed that the highest biomass, carbon stock, and CO2 sequestration values were found at station 2 with sequential sizes of 187.29 kg; 88.02 kg; 323.05 kg. The results of the correlation analysis indicate that carbon stock has a strong and significant positive correlation with diameter, biomass, and CO₂ uptake (r = 0.94, r = 1, and r = 1, respectively). Leaf area showed a strong but non-significant correlation (r = 0.73). Meanwhile, no significant correlations were found between tree height and leaf chlorophyll content and carbon stock (r = 0.20 and r = 0.38, respectively). These findings indicate that Terminalia mantaly has the potential to serve as a carbon sink and CO₂ sequester, particularly in the Surabaya State University Campus Forest.